Review on Dhatryadi Churna: An Ayurvedic Antipyretic Polyherbal Formulation - Sanket Shelke1 , Bharat Rathi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: In almost all Samhitas Jvara chikitsa is described with single or compound herbal drugs.Dhatryadi Churna is one such polyherbal churna formulation indicated in jvarachikitsa. But no data isavailable to know about its efficacy.Aim and Objectives: To review Dhatryadi Churna w.s.r. to its antipyretic activity.Material and Method: Relevant references were reviewed with respect to Dhatryadi Churna describedin Samhitas and various Ayurveda texts such as Brihatrayee, Laghutrayee bhaishajyaratnavali etc. All thereferences were collected and reviewed thoroughly.Observation and Results: Total 7 references with the name Dhatryadi Churna and Amalkyadi churna arerecorded in various Samhitas and Ayurveda texts indicated in jvara chikitsa. Out of the total 5 ingredients,significant antipyretic activity in experimental animals in different dosages found in Emblica officinalis,Terminalia chebula, Piper longum and Plumbago zeylenica.Conclusion: Based onPharmacological properties and experimental studies conducted on individual drugsproved that Dhatryadi churna is a effective antipyretic formulation and can be used safely for treating Jvara.